Measurement of D0 decays into Mathematical expression, Mathematical expression and Mathematical expression - Albrecht,H; Böckmann,P; Gläser,R; Harder,G; Krüger,A; Nippe,A; Reidenbach,M; Schäfer,M; Schmidt-Parzefall,W; Schröder,H; Schulz,HD; Sefkow,F; et al. (Zeitschrift Fur Physik C Particles and Fields, 1989)
Using the ARGUS detector at the electron-positron storage ring DORIS II at DESY, we have measured the branching ratios of the D0 meson decays into Mathematical expression, Mathematical expression and Mathematical expression relative to the K-π+ mode. Using the known branching ratio Br(D0→Kπ+)=(4.2±0.4±0.4)% we find Mathematical expression (90% CL) and Mathematical expression (90% CL). © 1989 Springer-Verlag.